A simple, sensitive and efficient electrochemical platform based on carbon paste electrode modified with Fe3O4@MIP and graphene oxide for folic acid determination in different matrices - Garcia, Sara Manente [UNESP]; Wong, Ademar [UNESP]; Khan, Sabir [UNESP]; Sotomayor, Maria D.P.T. [UNESP] (Elsevier, 2021)
A new biomimetic sensor selective to folic acid based on a carbon paste modified with graphene oxide and Fe3O4 nanoparticles coated with molecularly imprinted polymer in the core@shell format (Fe3O4@MIPs) was obtained using the polyol method. The sensing phase was synthesized in a simple way and characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and Brunauer-Emmett-Teller (BET) surface area. In the binding experiments the selective material showed a high adsorption capacity (Q) of 30.4 mg g−1 for MMIP, while the Q value for MNIP (magnetic non-imprinted polymer) was 15.3 mg g−1 both of them following the Langmuir model to the adsorption procedure. After their efficiency was proven, these materials were used as modifiers in the electrochemical sensor (Fe3O4@MIP-GO/CPE). Under optimized conditions using the square-wave adsorptive voltammetry, the proposed sensor exhibited excellent response with a concentration linear range between 2.5 and 48 μmol L−1 and limit of detection of 0.65 μmol L−1 (S/σ = 3). The advantages obtained with the proposed method were high robustness, selectivity, and low cost being these characteristics due to the MIP; highly sensibility due to the high superficial area being the contribution of the magnetite in the core of material; and experimentally versatile since was possible carry out numerous reproductible analysis only make the renovation of the paste electrode surface by simple polishing. The sensor was applied successfully in pharmaceutical formulation and river water samples with recoveries percentages near 100%.
Keywords: Core-shell material; Folic acid; Molecularly imprinted magnetic polymers; Polyol method